Epipaleolithic Site Discovery in Southeastern of Iran, Rayen - Mohammad Khodabakhshi Parizi; Mehdi mortazavi; Fariba Mosapour Negari (Iranian Journal of Archaeological Studies, 2014)
In the spring of 2012 an archaeological survey was conducted within the Rayen region in order to explore all the archaeological periods in this region and document all archaeological settlement patterns of this region. In general, 52 archaeological sites were discovered and documented which included all prehistoric and historic sites. Among these sites, three of them seem to belong to the Paleolithic period. This paper aims to describe one which, based on the available materials, technological and typological characteristics,is most likely from the Epi-Paleolithic, which is not well known from other parts of Iran. This specific era in Iranian Paleolithic studies and its existence and all its characteristics, complexity and their distributions around the country are highly unknown, especially from the southeastern Iran. Since this site is an open-air location, the only way to determine its approximate age is based on available materials. To achieve this, we have done analysis on the technological and typological characteristics of this site's lithics. In this paper, we describe the lithics and their technological and typological characteristics in order to determine the main production techniques and approximate age.